Organizational Decline in Education Offices in Jeddah Province from the Viewpoint of Educational Supervisors - Muharraq, Hussain Nasser Muhammad (Journal of Educational and Psychological Sciences, 2022)
The study aimed at the level of organizational decline in education offices in Jeddah from the point of view of the educational supervisors, and to reveal the extent of statistically significant differences between their points of view due to the two variables (gender, years of experience).To achieve the objectives of the study, the researcher used the descriptive survey method; where the researcher built a questionnaire of (35) phrases distributed over five dimensions. It was distributed to a stratified sample that included the whole community, which numbered (552) educational supervisors, in the education offices in Jeddah.The results of the study revealed: that the organizational decline in the education offices in Jeddah from the point of view of the educational supervisors got a total average of (2.07 out of 5), i.e. a decline of a (little) degree, at the level of dimensions, the dimension of creativity and innovation obstruction got the highest average (2.42), then the moral dimension decreased with an average of (2.29), thirdly, the dimension of resistance to change, with an average of (2.24), fourthly, the dimension of weakness of the regular administrative operations with an average of (1.89), and all of them have a degree of decline (little) and finally, the dimension of the conflict with an average of (1.57) and a degree of decline (very little), there are also no statistically significant differences at the level of significance (0.05≥α) between the averages of the responses of the educational supervisors due to the two variables; sex, and years of experience, with the exception of differences in the dimension (resistance to change) due to the variable years of experience, the differences were in favor of the experienced (less than 5 years, and from 5 to less than 10 years) versus those with years of experience (10 years or more).In light of the results of the study, the researcher recommended the necessity of paying attention to facilitating administrative procedures and practices and increasing financial allocations that contribute to the development of creativity and innovation, raising the moral of the supervisors, paying attention to change management, and finally paying attention to the supervisors' basic supervisory role and not occupying them with other side tasks, in addition to proposals for complementary studies on the subject.
Keywords: organizational regression; level of organizational regression; education offices; Educational Supervisors